Controlling the plasma electron number density of copper metal using NIR picosecond laser-induced plasma spectroscopy - Fikry, Mohamed; Tawfik, Walid; Omar, Magdy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
In this paper, we investigate a new method to control the plasma electron number density of copper metal using a near-infrared (NIR) picosecond Nd:YAG laser-induced plasma spectroscopy (LIPS) technique. The applied laser parameters are as follows; laser pulse energy and intensity varied from 29.2 to 59.4 mJ ± 3% and from 6.01×1010 to 12.35×1010 W/cm2 ± 5%, respectively, for a single pulse at 170 ps pulse duration, and beam diameter about 0.5 ± 0.1 mm. By considering the Stark broadening of a specific spectral line, electron density can be calculated using a neutral copper line at 521.8 nm, assuming the local thermodynamic equilibrium (LTE) condition. The observed electron density values were 1.09×1016, 2.24×1016, 3.60×1016, and 4.75×1016 cm–3 for the laser pulse energies 29.2, 41, 52.4, and 59.4 mJ, respectively. The plasma electron density values are increased with the increase in laser pulse energy. Such findings were interpreted due to an increase in the mass ablation rates with laser pulse energy. The obtained results explore the ability to control the plasma electron density by controlling the picosecond pulse energy. These results can contribute to the development of plasma technologies and their applications in many fields.
Optica Applicata, Vol. 51, 2021, nr 3, s. 365-374
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; picosecond; LIPS; copper; electron density; Stark broadening